Alcohol Biomarker Phosphatidylethanol as a Predictor of the Severity of Alcohol Withdrawal Syndrome. (24th January 2023) - Novak, Lan; Soravia, Leila M; Bünter, Adina; Stöth, Frederike; Wopfner, Alexander; Weinmann, Wolfgang; Pfeifer, Philippe
Abstract: Aims: to investigate the relationship between phosphatidylethanol (PEth) and withdrawal severity in patients with alcohol use disorder (AUD). Methods: in 34 patients with AUD admitted for treatment of acute alcohol withdrawal, data were available for initial blood PEth concentrations and scores throughout detoxification of symptoms of withdrawal assessed by trained medical staff using the alcohol withdrawal syndrome (AWS)-scale, a validated scale consisting of 11 items in the alcohol withdrawal syndrome (two subscales with seven physiological and five psychological symptoms). Results: a significant positive correlation between PEth and the severity of alcohol withdrawal was found. When the sample was divided into two groups, according to whether or not AWS score at some point in the treatment reached 6 or more, the median PEth score was higher in those whose peak score had been 6 or more (score of 6 being the suggested cutoff to start medicating the withdrawal syndrome). Although there was a trend for some aspects of the clinical history to be more 'severe' in those with higher AWS, no differences reached significance. Conclusion: blood PEth on admission could have a role in identifying patients at risk of more severe AWS.